Gambaran Pengetahuan Suami tentang Desa Siaga untuk Meningkatkan Kesehatan Ibu dan Bayi - Archisiang Rahartris Diva Prameswari; Vinami Yulian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the level of husbands' knowledge about DESA SIAGA in improving maternal and infant health in the working area of ​​Community Health Center B, S Regency. The research employed a quantitative approach with a descriptive design. The results showed that 50.7% of respondents had good knowledge, 45.3% had sufficient knowledge, and 4.0% had insufficient knowledge. The high knowledge category was most common among individuals aged 26–30, who had a high school/vocational high school/Islamic high school education, and those employed as private sector employees. These findings suggest that most husbands recognize their crucial role in supporting maternal and infant health through their participation in the DESA SIAGA program. In conclusion, husbands' knowledge contributes significantly to the successful implementation of the DESA SIAGA program, necessitating increased education and more intensive outreach to husbands as key partners in supporting maternal and infant health at the family and community levels. Keywords: DESA SIAGA, Maternal and Infant Health, Husbands' Knowledge, Community Empowerment